Etika Bermedia Sosial dalam Perspektif Islam: Integrasi Nilai-Nilai Etika Islam dan Literasi Digital - Khailla Azzira Prianto; Faqih Ibnu Risfi; Latifah Khoiriyah Nasution; Hernadia Salsabila Siregar; Raihan Ananda Faisal (Albayan Journal of Islam and Muslim Societies, 2026)
The development of social media in the digital era has brought about significant changes in communication and interaction patterns in society. Social media is not only a means of exchanging information but also influences users' behavior, mindsets, and communication culture. On the other hand, unethical use of social media often gives rise to various problems, such as the spread of hoaxes, hatred, cyberbullying, and privacy violations. This study aims to examine social media ethics from an Islamic perspective as a guideline for building polite, responsible communication that aligns with sharia values. The research method used is a literature review with a qualitative descriptive approach through analysis of the Qur'an, Hadith, and scientific literature related to Islamic communication ethics and social media use. The results show that Islam provides relevant ethical principles for the use of social media, including honesty in conveying information, checking news received, guarding speech, respecting the privacy of others, and avoiding slander and provocation. The application of these values ​​can create a healthier, more harmonious, and more civilized digital environment. Thus, social media ethics from an Islamic perspective plays a crucial role in shaping the character of wise and responsible social media users amidst the development of modern communication technology.